1992
DOI: 10.3354/dao012221
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of infectious pancreatic necrosis virus (IPNV) in scallops Pecten maximus

Abstract: Infectious pancreatic necrosis virus (IPNV), serotype N1 isolated from scallops Pecten maxjmus in Norway, was propagated and used in both inoculation and bath challenge experiments with scallops in vivo. Although virus titers measured in scallop tissues decreased, depuration of virus was not complete during the experimental periods. TPNV was still detectable 11 mo after injection. The highest virus titer was found in the hepatopancreas, but virus was also detectable in other tissues, as well as in the hemolymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…In such cases, the virus is probably sequestered in the digestive tissues. If a virus persists for a long period of time, we can expect a slow, long-term depuration process, with a possible release of virus (Mortensen et al 1992, Mortensen 1993. ISAV is an enveloped virus (Dannevig et al 1995, Falk et al 1997 and, thus, is considered relatively vulnerable to inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, the virus is probably sequestered in the digestive tissues. If a virus persists for a long period of time, we can expect a slow, long-term depuration process, with a possible release of virus (Mortensen et al 1992, Mortensen 1993. ISAV is an enveloped virus (Dannevig et al 1995, Falk et al 1997 and, thus, is considered relatively vulnerable to inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Some viruses are surprisingly inert and remain infectious for long periods of time, in water, sediments, particles and filter-feeding organisms. An example is IPNV, which could be recovered for long periods of time from digestive tissues of experimentally contaminated scallops (Mortensen et al 1992). In such cases, the virus is probably sequestered in the digestive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have showed that bivalve molluscs can rapidly accumulate virus from contaminated water (Shieh et al 1999, Muniain-Mujika et al 2003. The most significant example may be infectious pancreatic necrosis virus (IPNV), a fish epizootic pathogen that can also be isolated from scallop Pecten maximus but which appeared to be non-pathogenic for adult scallops (Mortensen et al 1992). In our study, the newly characterized MAbs improved our ability to diagnose infections caused by AVND virus and will make further investigations on the pathogenesis of this scallop etiologic virus possible.…”
Section: Avnd Virus Tissue Distribution and Histopathological Changesmentioning
confidence: 99%
“…For instance, blue mussels may have a beneficial effect in a net pen environment by reducing the amount of the kidney disease bacterium Renibacterium salmoninarum present (Paclibare et al 1994). Bivalves are also capable of retaining fish pathogenic viruses, but persistence periods vary greatly, presumably reflecting differences in the robustness of the viruses (Mortensen et al 1992, Skår & Mortensen 2007.…”
Section: Introductionmentioning
confidence: 99%